PENGARUH KOMPETENSI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. PEGADAIAN CABANG PEMBANTU ASEMBAGUS) - Pandhita, Aldhi; Karnadi, Karnadi; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to analyze the effect of the variable influence of Competence and Work Experience on Employee Perfomance Through Work Motivation as an Intervening Variable (Study at PT. Pegadaian Branch Asembagus) By using the Structrural Equation Model Partial Least Square (PLS) The result of the direct influence hypothesis test using the Smart PLS 3.0 application Competence has a significant effect on work motivation (H1 is a accepted), Work experience has a significant effect on work motivation, (H2 is accepted), Competence has a significant effect on employee perfomance, (H3 is a accepted), Work experience has a positive but not signifikan effect on performance employee, (H4 rejected), Work motivation has a significant efeect on performance employee, (H5 is a accepted), Competence has a significant effect on perfomance employee through work motivation, (H6 is a accepted), and Work eperience significant effect on employee performance through work motivation, (H7 is a accepted).